2018
DOI: 10.1109/tbcas.2017.2760504
|View full text |Cite
|
Sign up to set email alerts
|

PERSON—Personalized Expert Recommendation System for Optimized Nutrition

Abstract: The rise of personalized diets is due to the emergence of nutrigenetics and genetic tests services. However, the recommendation system is far from mature to provide personalized food suggestion to consumers for daily usage. The main barrier of connecting genetic information to personalized diets is the complexity of data and the scalability of the applied systems. Aiming to cross such barriers and provide direct applications, a personalized expert recommendation system for optimized nutrition is introduced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 23 publications
0
16
0
5
Order By: Relevance
“…The Food4Me Study published algorithms to integrate information based on current diet, phenotypic characteristics, and genotypic characteristics. 18 However, other approaches—for example, using machine-learning 19 or artificial intelligence, 20 might offer additional advantages.…”
Section: Personalisation Based On Biological Characteristics Of the Imentioning
confidence: 99%
“…The Food4Me Study published algorithms to integrate information based on current diet, phenotypic characteristics, and genotypic characteristics. 18 However, other approaches—for example, using machine-learning 19 or artificial intelligence, 20 might offer additional advantages.…”
Section: Personalisation Based On Biological Characteristics Of the Imentioning
confidence: 99%
“…It is not difficult to find that food identification, fruit, vegetable, fish, and meat quality detection tasks have begun to use deep learning technology, but only a very few of articles can be found that applied deep learning for food calorie estimation, food supply chain, and food contamination problems, and also for menu recognition (Lee, Chiu, & Chang, ), nutrition measurement (Pfisterer, Amelard, Chung, & Wong, ), food safety risk early warning (Geng, Shang, Han, & Zhong, ), personalized diet recommendation (C.H. Chen, Karvela, Sohbati, Shinawatra, & Toumazou, ), dining experience (Naritomi, Tanno, Ege, & Yanai, ), visual modeling of food (P.Y. Chen et al., ), and so on, which we did not describe in detail in the survey.…”
Section: Challenges and Future Perspective Of Deep Learning In Food Dmentioning
confidence: 99%
“…Estão disponíveis na literatura alguns trabalhos com algoritmos evolucionários que foram aplicados no contexto de geração de recomendações alimentares com diferentes abordagens. Em [5] e [6] os autores optaram por usar a otimização mono-objetivo com um AG (algoritmo genético) clássico. Já em [7] e [8] a abordagem multiobjetivo foi aplicada.…”
Section: A Algoritmos Evolucionários Aplicadosà Recomendação Alimentarunclassified
“…Na prática, os resultados do algoritmo com esta abordagem de avaliação se mostraram promissores durante os testes, com o aumento do número de recomendações oferecidas. Uma das limitações apontadas por [5]é o uso de porções de tamanho fixo dos alimentos, acarretando em recomendações limitadas a estas porções. Para contornar este problema, foi adotada a estratégia de permitir duas ou mais porções de um mesmo alimento em uma solução e utilizar recomendações com quantidade variável de alimentos para aumentar o número possível de resultados.…”
Section: A Definição Da Solução E Sua Aptidãounclassified